Sero-Epidemiology and Associated Risk Factors of Foot-and-Mouth Disease (FMD) in the Northern Border Regions of Pakistan - Munib Ullah; Yanmin Li; Kainat Munib; Hanif Ur Rahman; Zhidong Zhang (Veterinary Sciences, 2023)
The present cross-sectional survey was carried out to investigate the distribution and risk factors of FMD in Pakistan’s northern border regions. About 385 serum samples were compiled from small ruminants (239) and large ruminants (146) and tested using 3ABC-Mab-bELISA. An overall apparent seroprevalence of 67.0% was documented. The highest seroprevalence of 81.1% was reported in the Swat, followed by 76.6% in Mohmand, 72.7% in Gilgit, 65.6% in Shangla, 63.4% in Bajaur, 46.6% in Chitral and lowest 46.5% in Khyber region. Statistically significant variations in seroprevalence of 51.5%, 71.8%, 58.3%, and 74.4% were recorded in sheep, goats, cattle, and buffaloes, respectively. From the different risk factors investigated, age, sex, species of animal, seasons, flock/herd size, farming methods, outbreak location, and nomadic animal movement were found to be significantly associated (p < 0.05) with the seroprevalence of FMD. It was concluded that proper epidemiological study, risk-based FMD surveillance in small ruminants, vaccination strategy, control measures for transboundary animal movement, collaborations, and awareness programs need to be practiced in the study regions to investigate the newly circulating virus strains in large and small ruminants and associated factors for the wide seroprevalence to plan proper control policies to bound the consequence of FMD in the region.